2012
DOI: 10.1038/ijos.2012.48
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep bruxism on functional and occlusal parameters: a prospective controlled investigation

Abstract: This study was conducted to verify the results of a preceding retrospective pilot study by means of a prospective controlled investigation including a larger sample size. Therefore, the aim of this clinical investigation was to analyze the relationship between sleep bruxism and several functional and occlusal parameters. The null hypothesis of this study was that there would be no differences among sleep bruxism subjects and non-sleep bruxism controls regarding several functional and occlusal parameters. Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
1
18
0
3
Order By: Relevance
“…In the past, occlusal imbalance was considered as the primary etiological factor for bruxism; thus, dentists used to indicate occlusal adjustment [ 3 ] or occlusal stabilization splints [ 4 ]. However, SB is no longer considered to be related to occlusal discrepancies or is not considered to be a result of stress, anxiety, or depression [ 5 , 6 , 7 ]. The most recent hypotheses on the etiology of SB support the roles of the central and autonomic nervous systems in the genesis of masticatory muscle activity during sleep [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, occlusal imbalance was considered as the primary etiological factor for bruxism; thus, dentists used to indicate occlusal adjustment [ 3 ] or occlusal stabilization splints [ 4 ]. However, SB is no longer considered to be related to occlusal discrepancies or is not considered to be a result of stress, anxiety, or depression [ 5 , 6 , 7 ]. The most recent hypotheses on the etiology of SB support the roles of the central and autonomic nervous systems in the genesis of masticatory muscle activity during sleep [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common degenerative condition observed in temporomandibular joint disorder (TMD) is osteoarthritis (OA), which causes severe pain and discomfort on one or both sides of the face. 1 , 2 One percent of Hong Kong Chinese individuals have frequent TMD-related jaw pain, 3 and 14.56% of mainland Chinese patients with TMD exhibit radiographic signs of OA. 4 Temporomandibular joint OA (TMJ-OA) is a common condition that limits the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Bruxism is defined as the grating or scrunching of the teeth in the time of sleep less frequently during the day [1]. It was reported that bruxism is persistent trait with genetic effect in both childhood and adult ages as according to a study it was revealed that genetic bruxism in childhood was 64% in females and for adults 53% among females [2].…”
Section: Introductionmentioning
confidence: 99%